Microclimate modelling of mesua ferrea L., Mimusops Elengi L. and pheltophorum pterocarpum (DC) K. Heyne in Universiti Putra Malaysia - Mah, Chen Ying (2014)
The Urban Heat Island Effect is a common topic in research literature and newspapers nowadays. The aim of this study is to identify and evaluate the conditions of isolated landscape tree towards microclimate as compared to the open space without tree, as well as the comparison of microclimate under three various popular landscape trees, namely: Peltophorum pterocarpum (umbrella form), Mimusops elengi (round form), Mesua ferrea (conical form). Two sets of watch dog 2000 weather stations are used to collect the solar radiation, air temperature and relative humidity. One set is placed under the tree, another set is placed in the open space without tree. An AccurPAR LP80 is used to collect Leaf Area Index data. The study site is at University Putra Malaysia. The data analysis was conducted using R software (The R Foundation Statistical Computing) and Minitab statistical software. The research hypothesis is to study the microclimate conditions under tree species. The findings reveal that the tree species has a great reduction on solar radiation under tree canopy as compared to open space without tree. The solar radiation for Mimusops elengi (reduction 95.55%) is the lowest amongst the three species, Mesua ferrea ranked second, Peltophorum pterocarpum is third. However, the air temperature and relative humidity have no significantly different effects in ststisticsas compared to open space without tree, but the air temperature has slightly lower and relative humidity has a slight increment under tree canopy. The hypotensis testing develops the microclimate model which can be used as a tool for predicting the curve and estimating the percentage of decrement or increment of microclimate under the tree species. The trees with an umbrella form and round form are able to provide bigger shade compared to Mesua ferrea which has a conical form. The shade is able to intercept sunlight and diminish the solar radiation which affects the comfort of humans. Therfore, the size of canopy area is very important to influence urban heat island effect. The results from this study suggest that the selection of appropriate urban trees by the planners and landscape architects to ameliorate the Urban Heat Island effect in the design approach should also consider the tree species, which can provide bigger shade and higher Leaf Area Index.